Poligami dalam Perspektif Kader Muslimah Wahdah Islamiyah Makassar - Iskandar, Iskandar; Novira, Nuraeni; Syahriani, Eka; Aswar, Aswar (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2020)
This study aimed to determine the concept of polygamy in Islam and to identify polygamy from the perspective of the Muslimah Wahdah Islamiyah's cadres in Makassar. The problems that the authors raise in this study are; First, what is the concept of polygamy in Islam. Second, what is the perspective of Muslimah Wahdah Islamiyah Makassar's cadres on polygamy. To find answers to these problems, the author employed a quantitative approach which is designed as survey research using a questionnaire for data collection. Then the understanding of the results of the analysis is interpreted descriptively. The results of the study found that the perspective of Muslimah Wahdah Islamiyah's cadres in Makassar on polygamy can be seen based on two things, namely the level of knowledge and understanding of the Muslimah Wahdah Islamiyah's cadres in Makassar towards polygamy which is in the medium category and the level of agreement of statements regarding the perceptions and attitudes of Muslimah Wahdah Islamiyah Makassar's cadres against polygamy which is classified as positive and falls into the "approved" category